EFFICACY OF TARGET THERAPY WITH CRIZOTINIB IN A PATIENT WITH ALK-POSITIVE ADVANCED GASTRIC CANCER - A. A. Paichadze; L. V. Bolotina; E. Y. Karpenko; T. V. Ustinova; A. L. Kornietskaya; A. D. Kaprin; A. A. Fedenko (Сибирский онкологический журнал, 2020)
Although many currently known molecular targets are characterized by organ specificity, they can be found in various types of tumors. Molecular diagnostic techniques can be used to help select patients who are most likely to benefit from target therapy. Case presentation. We describe the case of a 38-year-old patient with advanced gastric cancer with peritoneal dissemination. On december 11, 2014, the patient underwent palliative subtotal gastrectomy followed by 18 cycles of chemotherapy (xelOx) and radiotherapy. On February 2, 2017, percutaneous transhepatic cholangiostomy of the left lobe bile duct was performed. in May 2017, the stent was inserted into the common bile duct due to bile duct stenosis. three months later, disease progression (multiple liver metastases) occurred, and chemotherapy with paclitaxel was given in a weekly schedule. therapy with crizotinib was administered 3 months after determining the alK mutation. the duration of treatment was 8 months with satisfactory tolerability. Conclusion. target therapy with krizotinib seems to be an effective treatment for alK-positive tumors.